2020
DOI: 10.1101/2020.03.18.20038190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A brief review of antiviral drugs evaluated in registered clinical trials for COVID-19

Abstract: BackgroundAlthough a number of antiviral agents have been evaluated for coronaviruses there are no approved drugs available. To provide an overview of the landscape of therapeutic research for COVID-19, we conducted a review of registered clinical trials. MethodsA review of currently registered clinical trials was performed on registries, including the Chinese (chictr.org.cn) and US (clinicaltrials.gov) databases to identify relevant studies up to March, 7 th 2020. FindingsOut of the 353 studies identified, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 34 publications
0
58
0
2
Order By: Relevance
“…Antiviral treatments are warranted to contain the epidemics. Several candidates are already being investigated, including type 1 interferon (IFN-I) (Martinez, 2020;Belhadi et al, 2020). Indeed, in the context of emerging viral infections, IFN-I are often evaluated (usually in combination with other drugs) before specific treatments are developed, due to their unspecific antiviral effects (Gao et al, 2010;Loutfy et al, 2003;Omrani et al, 2014).…”
Section: Main Textmentioning
confidence: 99%
“…Antiviral treatments are warranted to contain the epidemics. Several candidates are already being investigated, including type 1 interferon (IFN-I) (Martinez, 2020;Belhadi et al, 2020). Indeed, in the context of emerging viral infections, IFN-I are often evaluated (usually in combination with other drugs) before specific treatments are developed, due to their unspecific antiviral effects (Gao et al, 2010;Loutfy et al, 2003;Omrani et al, 2014).…”
Section: Main Textmentioning
confidence: 99%
“…These strategies include remdesivir (Gilead Sciences), a nucleoside analogue that inhibits SARS-CoV-2 RNA-dependent RNA polymerase activity and viral replication ( 3 ), immune inhibitors, like the KEVZARA trial in which the efficacy of an anti-interleukin 6 (IL-6) receptor antibody is evaluated to stop an overactive inflammatory response, and development of monoclonal antibodies as therapy, as well as ongoing efforts with immediately available convalescent plasma ( 4 ). Also, type 1 interferons (especially alpha interferon [IFN-α] and IFN-β) with broad antiviral activity are being evaluated in clinical trials to treat SARS-CoV-2 ( 5 , 6 ). In vitro studies successfully confirmed the sensitivity of SARS-CoV-2 to type 1 interferons ( 7 ).…”
Section: Treatment and Intervention Strategiesmentioning
confidence: 99%
“…While the remdesivir was associated with the highest median number of the planned inclusions per trial (400, IQR 394-453) only for 5 trials. [15][16][17] Zhang et al 18 considered 125 clinical trials on the treatment of COVID-19, registered up to February 18, 2020, which were conducted by pharmaceutical companies, government, institutions, physicians, and scientists. Accordingly, the results showed that 33.3% of all the clinical trials used anti-viral agents, 14.7% antiinflammation or immune modulators, 33.3% herbs or traditional Chinese medicine (TCM), 9.3% cell-based therapy, 2.3% anti-oxidation, and 7.0% of them used other methods.…”
Section: Antiviral Drugs and Anti-inflammatory Agentsmentioning
confidence: 99%